Role of the breast cancer surgeon in the personalized era. (May 2013) - Ahmadiyeh, Nasim; Schnure, Nilan; Esserman, Laura
SUMMARY Significant advances in our understanding of the biology of breast cancer have afforded opportunities to tailor breast cancer treatment, screening and prevention. The surgeon is a vital member of the multidisciplinary team, and is often the first physician to recommend treatment. A comprehensive knowledge of biology, the range of treatment outcomes associated with the various treatment modalities and surgical and oncoplastic techniques is essential for today's surgeon. Given that there is a range of treatments that are possible, the surgeon must also be skilled in shared decision-making and serve as a guide to the patient in assisting them in selecting treatments that are most appropriate for their specific situation. In addition, the surgeon should be an advocate for clinical trials and registries that serve to further enable us to optimize treatment according to biology, patient preference and clinical performance.